Hungarian unions: Responses to political challenges - László Neumann (Management Revue, 2012)
Hungarian trade unions face both the direct consequences of economic downturn and the political challenges that are implied by the deterioration in employees' and unions' bargaining positions with regard to employers. This article presents the political responses of both militant and moderate trade unions in detail. Compromises in Labour Code legislation and the creation of a new top-level negotiation forum are signs of a moderate union success.
Keywords: J51; J52; J83; K31; 650; Hungary; social dialogue; trade union legislation; union renewal; civic movements